2008
DOI: 10.1021/es800654p
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influences between Natural Organic Matter and Inorganic Particles and Their Combined Effect on Ultrafiltration Membrane Fouling

Abstract: Fouling is one of the most critical aspects of membrane technology and is strongly influenced by natural water characteristics.This studyfocuses on a mechanistic understanding of the impact of interactions between natural organic matter (NOM) and particles on fouling. The model substances used were humic acid, alginate (polysaccharide), and kaolinite. NOM-kaolinite adsorption experiments, particle characterization, and dead-end ultrafiltration (UF) batch experiments were performed. The adsorption experiments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Varbanets et al [10] found that hydrophobic humic acids made an increase in resistance at ultra-low pressure UF membrane system by investigating seven types of water. Jermann et al [11] set up a series of dead-end UF batch experiments to observe the fouling of humic acid, alginate and kaoline. They reported that humic substances caused severe irreversible fouling due to adsorption, while alginate should have a most detrimental effect on membrane fouling, but mostly reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Varbanets et al [10] found that hydrophobic humic acids made an increase in resistance at ultra-low pressure UF membrane system by investigating seven types of water. Jermann et al [11] set up a series of dead-end UF batch experiments to observe the fouling of humic acid, alginate and kaoline. They reported that humic substances caused severe irreversible fouling due to adsorption, while alginate should have a most detrimental effect on membrane fouling, but mostly reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested that NOMs especially humic substances could improve the stability of particle suspension, and that divalent cations would destabilize them [16,17]. More recently, some specific fractions of NOMs were found to be effectively destabilized in the presence of particles [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other researches [27] also reported the addition of coagulants aggravated fouling in coagulation-membrane filtration process. Researches on combined fouling of NOM-particle on membrane filtration process have been published in the past few decades [18,28,29]. These contradictory results might be attributed to the fact that the mutual interaction among colloidal-NOM has important effect on membrane fouling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of NOM is expected to influence the membrane fouling mechanism. Earlier studies have observed a synergistic effect between NOM and common inorganic colloids on membrane fouling [14][15][16]. Jermann et al [15] found a significant stronger flux decline during the filtration of mixed solutions consisting of humic acid and kaolinite particles, in comparison with individual foulants.…”
mentioning
confidence: 99%
“…Earlier studies have observed a synergistic effect between NOM and common inorganic colloids on membrane fouling [14][15][16]. Jermann et al [15] found a significant stronger flux decline during the filtration of mixed solutions consisting of humic acid and kaolinite particles, in comparison with individual foulants. Compared with common inorganic particles, the high surface-area-to-volume ratio makes the behavior of nanoparticles during membrane filtration significantly different.…”
mentioning
confidence: 99%